Prevalence of Diabetes Type 2 in Hepatitis C Infected Patients in Kpk, Pakistan. (4th April 2017) - Rehman, Ghani Ur; Ali, Mohammad; Shah, Farooq; Iqbal, Amjad; Ahmad, Ayaz; Hayat, Zafar; Islam, Badshah; Ali, Farman; Ikramullah; Jamal, Yousaf; Alam, Sartaj; Sajjad, Muhammad; et al.
Abstract : Hepatitis C (HCV) and diabetes mellitus are the two main health concerns that cause devastating health and financial worries worldwide. It has been observed in the past that both diseases have a high correlation that might be due to the abnormal conditions of the liver. But the mechanism of the prevalence of diabetes in patients with chronic HCV infection still remains unclear. In our study, we have investigated T2DM in the male and female patients at Lady Reading Hospital (LRH), Peshawar. The blood samples of both in- and outpatients were analysed in the PCR laboratories of LRH from December 2014 to April 2015. Great prevalence of diabetes in hepatitis C infected male and female patients was observed during this study. The data were collected from the patients through a preplanned questionnaire that included name of the patient, HCV, being diabetic, age, gender, location, educational background, family history of the disease, other diseases, and any treatments if taken. The results of our study have found 26.42% prevalence of T2DM in HCV infected patients. So we conclude that HCV infection may be one of the reasons that could lead to T2DM.